Potential Symmetries, Lie Transformation Groups and Exact Solutions of Kdv-Burgers Equation - Wang, XiaoMin; Bilige, Sudao; Bai, YueXing (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, the classical symmetries and the potential symmetries of KdVBurgers equation are calculated based on differential characteristic set algorithm, and the corresponding Lie transformation groups and invariant solutions of the potential symmetry are derived. Moreover a series of new exact solutions for KdV-Burgers equation are obtained by acting Lie transformation groups on the invariant solutions. It is important that these solutions can not be obtained from the classical symmetries of KdV-Burgers equation.